2013
DOI: 10.1530/eje-12-1107
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus among Norwegian women with polycystic ovary syndrome: prevalence and risk factors according to the WHO and the modified IADPSG criteria

Abstract: Objective: The consequences of the recently proposed International Association of Diabetes in Pregnancy Study Group (IADPSG) criteria for gestational diabetes mellitus (GDM) in women with polycystic ovary syndrome (PCOS) are not known. We compared the prevalence rates and risk factors for GDM in PCOS women according to both the WHO and the modified IADPSG criteria. Design: Post hoc analyses from a randomized, multicenter study were used. Methods: Fasting and 2-h plasma glucose levels were measured using a 75 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…343 review articles were excluded and additionally 463 articles were excluded because of irrelevance. Thirty studies fullfilled inclusion criteria; 10 prospective [31][32][33][34][35][36][37][38][39][40] and 20 retrospective studies [4, 10-15, 23, 41-52]. Included studies reported data on 11,263 women with PCOS and 1,389,161 controls.…”
Section: Narrative Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…343 review articles were excluded and additionally 463 articles were excluded because of irrelevance. Thirty studies fullfilled inclusion criteria; 10 prospective [31][32][33][34][35][36][37][38][39][40] and 20 retrospective studies [4, 10-15, 23, 41-52]. Included studies reported data on 11,263 women with PCOS and 1,389,161 controls.…”
Section: Narrative Reviewmentioning
confidence: 99%
“…Twelve different sets of diagnostic criteria for GDM were used in the 30 studies ( Table S2). The most frequently used criteria were those of the American College of Obstetricians and Gynecologists (ACOG) [53] (n=7) [23,32,33,39,42,45,49], followed by American Diabetes Association (ADA2000) [54] (n=6) [13,34,[41][42][43]52], WHO1999 [55] (n=5) [33,35,37,38,51], WHO13/International Association of the Diabetes and Pregnancy Study Group (IADPSG) [26,56] (n=3) [15,40,47], Danish criteria (GDM-DK) [18] (n=2) [4,46] and the Modified IADPSG (n=2) [35,37]. The following criteria were only applied in one study each: National Diabetes Data Group (NDDG) [57] (n=1) [12] and Australasian Diabetes in Pregnancy Society (ADIPS) [58] (n=1) [50].…”
Section: Narrative Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The varying association of PCOS with GDM depends on the population studied due to genetic factors where the metabolic syndrome in parents and their siblings seems to be fundamental to the pathogenesis of PCOS [14,15]. Franks et al conclude that PCOS is inherited on an oligogenic basis and the co-morbidity and phenotype are due to the interaction of a small number of key genes with environmental and nutritional factors [16].…”
Section: Discussionmentioning
confidence: 99%